2022
DOI: 10.1111/aogs.14425
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric anal sphincter injuries—Maternal, fetal and sociodemographic risk factors: A retrospective register‐based study

Abstract: Introduction: Obstetric anal sphincter injuries (OASIS) are severe complications to vaginal births with potentially serious long-term consequences and large impact on quality of life. The aim was to determine risk and protective factors for OASIS. Material and methods: We performed a retrospective register-based observational study. A cohort of 988 988 singleton term deliveries 2005-2016 in Sweden were included. Data from the Swedish Medical Birth Registry and Statistics Sweden were extracted to identify cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
0
3
0
1
Order By: Relevance
“…We also did not retrieve the number of prostaglandins used in cases of adverse outcomes. Obstetric sphincter injury (OASIS) was not explored in our study; previous cesarean section increases the risk of OASIS [ 51 ] but OASIS does not appear to be associated with IOL per se [ 52 ]. We used delivery blood loss ≥ 1000 ml as an adverse maternal outcome for the composite instead of the need for blood transfusion, which could be a more objective and clinically useful measure.…”
Section: Discussionmentioning
confidence: 99%
“…We also did not retrieve the number of prostaglandins used in cases of adverse outcomes. Obstetric sphincter injury (OASIS) was not explored in our study; previous cesarean section increases the risk of OASIS [ 51 ] but OASIS does not appear to be associated with IOL per se [ 52 ]. We used delivery blood loss ≥ 1000 ml as an adverse maternal outcome for the composite instead of the need for blood transfusion, which could be a more objective and clinically useful measure.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies show that overweight and obese women have a lower risk of OASI compared to women with normal weight [3][4][5] . However, a recently published study shows contrasting results, indicating that women with obesity are at higher risk of sustaining an OASI 24 . The contradicting results may depend on combinations of variables adjusted for.…”
Section: Maternal Overweight and Obesitymentioning
confidence: 93%
“…How ethnicity or race is defined varies between different studies. In our previous study 7 we found an increased risk of OASIS in those born outside of Europe which we wanted to explore further. Asian ethnicity has been associated with a significantly increased risk of OASIS, 8–10 and women from South Asia have been identified as being particularly high risk 11 .…”
Section: Introductionmentioning
confidence: 94%